Component of tourism and hospitality in international business - Shapoval, V. S.; Mekhovych, S. A.; Pererva, P. G. (My University, 2023)
The report proves that the entire complex of factors influencing the development of international tourism business is divided into two groups. The first includes factors acting independently of the activities of organizations of the tourism industry. The second group includes factors that have a favorable effect on tourism, which are actively used by tourist companies in their activities.
Складова туризму та гостинності в міжнародному бізнесі
Keywords: international business; tourism industry; hospitality; market; demand; supply